Effectiveness of chlorhexidine on the disinfection of complete dentures colonised with fluconazole-resistant Candida albicans: in vitro study - de Oliveira Mima, Ewerton Garcia; Pavarina, Ana Claudia [UNESP]; Vargas, Fernanda da Silveira [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Wiley-Blackwell, 2011)
This in vitro study evaluated different concentrations of chlorhexidine (CHX) solution on the disinfection of dentures colonised with a reference (ATCC 90028) and azole-resistant (R1, R2 e R3) strains of Candida albicans. Sterile dentures were individually inoculated with one of the strains and incubated at 37 degrees C for 24 h. Then, each denture was immersed in sterile saline (control) or CHX (2%, 1% or 0.2%) for 10 min. Samples of serial dilutions were spread on Agar Sabouraud Dextrose and incubated at 37 degrees C for 48 h. The colonies were counted and the values of log(cfu ml(-1)) were analysed by Kruskal-Wallis test (P < 0.05). Dentures immersed in CHX were incubated for 7 days. For all strains, the cfu ml(-1) values of 0.2% CHX were significantly higher than those of 2% and 1% CHX. There was no difference between the cfu ml(-1) values of 2% and 1% CHX. For dentures immersed in CHX, ATCC 90028 strain showed lower cfu ml(-1) values than R2 and R3 strains. For control dentures, cfu ml(-1) values of ATCC 90028 strain were higher than those of R strains. Immersion in 2% CHX resulted in the highest number of dentures without fungal growth after 7 days. For denture disinfection, 2% CHX was the most effective concentration, and R strains were less susceptible to disinfection. Chlorhexidine is effective in disinfection of dentures contaminated with azole-resistant C. albicans.
Keywords: Candida albicans; fluconazole-resistance; complete dentures; chlorhexidine; azole resistance; disinfection